Pearsonema plica and Eucoleus böhmi infections and associated lesions in wolves (Canis lupus) from Italy - MARIACHER, A.; Eleni, C.; Fico, R.; Ciarrocca, E.; PERRUCCI, STEFANIA (Helminthologia, 2015)
Reports of Pearsonema plica and Eucoleus böhmi infections in wolves (Canis lupus) in Europe are limited and data on associated lesions are lacking. In the present study urinary bladders, nasal turbinates and faecal samples from 8 necropsied wolves were examined for P. plica and E. böhmi infections and associated lesions. P. plica was identified in the bladder of four wolves. At histological examination, follicular chronic cystitis and eosinophilic cystitis were found. E. böhmi nematodes and eggs were identified from the nasal turbinates and rectal faecal samples of three wolves. Worms and eggs were found embedded in the mucosa among the nasal bone laminae. Two wolves were found coinfected by P. plica and E. böhmi. This is the first report of P. plica and E. böhmi infections in wolves from Italy and the first description of pathological lesions associated with P. plica infection in wolves.